Imagery and spatial processes in blindness and visual impairment - Cattaneo, Zaira; Vecchi, Tomaso; Cornoldi, Cesare; Mammarella, Irene; Bonino, Daniela; Ricciardi, Emiliano; Pietrini, Pietro (Neuroscience and biobehavioral reviews, 2008)
The objective of this review is to examine and evaluate recent findings on cognitive functioning (in particular imagery processes) in individuals with congenital visual impairments, including total blindness, low-vision and monocular vision. As one might expect, the performance of blind individuals in many behaviours and tasks requiring imagery can be inferior to that of sighted subjects; however, surprisingly often this is not the case. Interestingly, there is evidence that the blind often employ different cognitive mechanisms than sighted subjects, suggesting that compensatory mechanisms can overcome the limitations of sight loss. Taken together, these studies suggest that the nature of perceptual input on which we commonly rely strongly affects the organization of our mental processes. We also review recent neuroimaging studies on the neural correlates of sensory perception and mental imagery in visually impaired individuals that have cast light on the plastic functional reorganization mechanisms associated with visual deprivation.